Preparation method and application of flame-retardant cellulose-based diaphragm for lithium battery
By conducting specific chemical reactions on the cellulose diaphragm, the flame-retardant cellulose-based diaphragm is solved, and the problems of high interface impedance and flammability of the existing cellulose diaphragm are improved efficiently and the safety performance is achieved.
Patent Information
- Application Number
- CN202410714037.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-04
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-06-04
AI Technical Summary
The existing cellulose separators have problems with high interface impedance and flammability, which affects the electrochemical performance and safety performance of lithium batteries.
By reacting substances such as anhydrous ethanol, 4-aminopyridine, anhydrous potassium carbonate and hexachlorocyclotriphosphazene, a flame-retardant cellulose-based separator is formed, which improves the flame-retardant and electrochemical properties of the separator.
The prepared flame-retardant cellulose-based separators have high ionic conductivity, porosity and electrolyte wetting, low thermal expansion and flammability, which significantly improves the electrochemical performance and safety performance of lithium batteries.
Smart Images

Figure CN118472553B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium battery separators, and in particular, relates to a preparation method and application of a flame-retardant cellulose-based separator for lithium batteries. Background Art
[0002] Lithium-ion batteries (LIBs) have the advantages of high energy density and long cycle life, and have been widely used in electric vehicles and energy storage power stations. As one of the important components of the battery, the separator has the key function of physically separating the anode and cathode and facilitating the transport of ionic charge carriers between the electrodes. The mechanical strength and thermal stability of the separator are the basic guarantees for the safety of lithium batteries. At the same time, the high porosity and electrolyte wettability of the separator are necessary conditions for the high electrochemical performance of lithium batteries.
[0003] Polyolefin membrane is the most widely used diaphragm with good electrochemical stability, mechanical strength and low cost. However, there are many disadvantages, including porosity values in the range of 40-60%, thermal shrinkage of up to 40% at 150°C, low electrolyte absorption rate, and contact angle greater than 20°, which seriously damage the electrochemical and safety performance of lithium batteries. Therefore, flame retardant treatment of the diaphragm is an important strategy to improve the safety performance of lithium batteries. Among them, flame retardant coating is a feasible solution. For example, the Chinese invention patent with publication number CN116823313A proposes to use Mg(OH)2@LATP composite material to coat the surface of polyolefin diaphragm to enhance flame retardancy. However, the coating of the composite material will cause the porosity of the diaphragm to decrease, which may have an adverse effect on the electrochemical performance of the diaphragm. In addition, polyolefin diaphragm is a petroleum-based material, which is neither renewable nor biodegradable. Therefore, there is an urgent need for new diaphragms for high-performance and environmentally friendly lithium batteries.
[0004] As a promising material, cellulose has been widely used in various applications for centuries due to its natural abundance, biocompatibility and renewability. Compared with some polymer materials, it has a wide range of sources, light weight, excellent electrolyte wettability and thermal stability, and therefore has become a potential alternative to typical polyolefin separators. However, cellulose fibers undergo pyrolysis after being heated, and the pyrolysis products are solid, liquid or gaseous substances. Flammable liquids and gaseous substances are ignited and burned, and the heat generated intensifies the combustion. In recent years, research on cellulose separators for lithium batteries has been widely reported. For example, the Chinese patent with publication number CN115498358A proposes that cellulose, lignin and ammonium polyphosphate are mixed and freeze-dried to form a film, and then heated and rolled to obtain a cellulose separator for lithium batteries. The cellulose separator prepared by this method exhibits good mechanical properties and flame retardant properties. However, the thickness of the cellulose separator prepared by this method is as high as 60 to 100 μm, which is much larger than that of polyolefin separators (20 to 30 μm), which may lead to a series of electrochemical properties such as lithium battery cycle performance cannot be effectively guaranteed. In addition, complex preparation processes and harsh preparation conditions are also dilemmas faced by cellulose separators for lithium-ion batteries.
[0005] Therefore, under the premise of not destroying the electrochemical properties of lithium-ion batteries, it is a problem that technicians in this field need to solve to simply prepare an efficient flame-retardant cellulose-based separator.
[0006] In summary, existing cellulose separators have problems with high interfacial impedance and flammability. Summary of the invention
[0007] In view of this, the present invention provides a method for preparing a flame-retardant cellulose-based diaphragm for a lithium battery and its application, which can solve the problems of high interface impedance and flammability of existing cellulose diaphragms.
[0008] The present invention is achieved in that:
[0009] The first aspect of the present invention provides a method for preparing a flame-retardant cellulose-based separator for a lithium battery, which comprises the following specific steps:
[0010] S10: adding anhydrous ethanol into the flask containing 4-aminopyridine, heating and stirring until it is completely dissolved;
[0011] S20: adding anhydrous potassium carbonate to the mixed solution to form a mixed solution;
[0012] S30: adding a chlorobenzene solution containing hexachlorocyclotriphosphazene to the mixed solution, and stirring for a certain period of time to react;
[0013] S40: repeatedly filtering and extracting the crude product obtained by the reaction through chlorobenzene and ethanol;
[0014] S50: soaking the cellulose diaphragm dried in advance with the filtrate to obtain a flame retardant cellulose-based diaphragm.
[0015] The technical effects of the method for preparing a flame-retardant cellulose-based diaphragm for a lithium battery provided by the present invention are as follows:
[0016] By adding anhydrous ethanol into a flask containing 4-aminopyridine and heating and stirring until it is completely dissolved, it is ensured that the 4-aminopyridine can be fully dissolved in the anhydrous ethanol, and uniform reaction conditions are provided for the next reaction; by adding anhydrous potassium carbonate into the mixed solution to form a mixed solution, the subsequent reaction can be promoted and the formation of the product can be facilitated; by adding a chlorobenzene solution containing hexachlorocyclotriphosphazene into the mixed solution and stirring for a certain time to react, it is helpful to improve the flame retardant performance of the diaphragm, thereby enhancing the safety performance of the lithium battery; by repeatedly filtering and extracting the crude product obtained by the reaction through chlorobenzene and ethanol, impurities can be removed, the purity of the product can be improved, and the quality of the diaphragm can be improved; by taking the filtrate to soak the cellulose diaphragm dried in advance, a flame-retardant cellulose-based diaphragm is obtained, so that the diaphragm has flame retardant performance and the application safety in the lithium battery is improved.
[0017] 4-aminopyridine plays a role of dissolving and reacting in the above-mentioned preparation method. Specifically, 4-aminopyridine is mixed with anhydrous ethanol and heated and stirred until completely dissolved, which helps to fully dissolve it in anhydrous ethanol and provides uniform reaction conditions for subsequent steps. In addition, the addition of anhydrous potassium carbonate catalyzes the reaction of hexachlorocyclotriphosphazene with 4-aminopyridine to form the final flame-retardant cellulose-based diaphragm product. Therefore, 4-aminopyridine plays an important role of dissolving and reacting in the entire preparation process.
[0018] Hexachlorocyclotriphosphazene (also known as hexachlorophosphinate) is a commonly used flame retardant that can effectively improve the flame retardant properties of materials.
[0019] On the basis of the above technical solution, the method for preparing a flame-retardant cellulose-based diaphragm for a lithium battery of the present invention can also be improved as follows:
[0020] Wherein, in the step of adding anhydrous ethanol into a flask containing 4-aminopyridine and heating and stirring until completely dissolved, the mass ratio of anhydrous ethanol to 4-aminopyridine is 20-25:1-4.
[0021] Furthermore, in the step of adding anhydrous ethanol into a flask containing 4-aminopyridine and heating and stirring until the 4-aminopyridine is completely dissolved, the heating temperature is 30 to 60°C.
[0022] Furthermore, anhydrous potassium carbonate is added to the above-mentioned mixed solution, and the mass ratio of anhydrous potassium carbonate to 4-aminopyridine is 3-6:1-4.
[0023] Furthermore, in the step of adding the chlorobenzene solution containing hexachlorocyclotriphosphazene to the mixed solution and stirring for a certain period of time, the mass ratio of chlorobenzene, hexachlorocyclotriphosphazene and 4-aminopyridine is 10-15:1-4:1-4.
[0024] Furthermore, in the process of adding the chlorobenzene solution containing hexachlorocyclotriphosphazene into the mixed solution and stirring for a certain period of time to react, the stirring time is 1 to 3 hours.
[0025] Furthermore, in the process of repeatedly filtering and extracting the crude product obtained by the reaction through chlorobenzene and ethanol, the volume ratio of anhydrous ethanol to chlorobenzene is 40-60:10-20; and the number of filtering times is 1 to 5 times.
[0026] Furthermore, in the soaking process of soaking the cellulose membrane dried in advance with the filtrate, the cellulose membrane is soaked in the filtrate for 1 to 5 hours and the number of times the cellulose membrane is soaked is 1 to 5 times.
[0027] The second aspect of the present invention provides an application of a flame retardant cellulose-based diaphragm for a lithium battery. The flame retardant cellulose-based diaphragm is used to assemble a lithium ion battery, and after standing for a period of time, a flame retardant cellulose-based LIB diaphragm is obtained.
[0028] On the basis of the above technical solution, the application of a flame-retardant cellulose-based diaphragm for a lithium battery of the present invention can also be improved as follows:
[0029] Furthermore, the density of the flame-retardant cellulose-based LIB separator is 0.3 to 0.6 g / cm 3 .
[0030] Compared with the prior art, the preparation method of a flame-retardant cellulose-based diaphragm for a lithium battery provided by the present invention and the beneficial effects of its application are:
[0031] (1) The preparation process of the present invention is simple and controllable, and is feasible for industrial large-scale production. Moreover, the preparation process is time-saving, and the preparation of the flame-retardant cellulose-based diaphragm is a new way to utilize cellulose resources, which meets the requirements of sustainable development.
[0032] (2) The flame-retardant cellulose-based diaphragm prepared by the present invention has the advantages of high ion conductivity, large porosity, and good electrolyte wettability. The lithium-ion battery prepared with the flame-retardant cellulose-based diaphragm exhibits excellent electrochemical performance in electrochemical tests.
[0033] (3) The flame-retardant cellulose-based diaphragm of the present invention has the advantages of low thermal expansion and contraction rate, good thermal stability and low flammability. It carbonizes rapidly when heated and exhibits excellent flame-retardant properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments of the present invention will be briefly introduced below. Obviously, the accompanying drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative labor.
[0035] Figure 1 The present invention is an operation flow chart of a method for preparing a flame-retardant cellulose-based diaphragm for a lithium battery;
[0036] Figure 2 This is a test diagram of the electrolyte contact angle of the flame-retardant cellulose-based separator for lithium batteries in Example 1;
[0037] Figure 3 This is a test diagram of thermal stability of the flame-retardant cellulose-based diaphragm for lithium batteries in Example 1;
[0038] Figure 4 This is a comparison chart of the first charge and discharge capacities of the flame-retardant cellulose-based separator for lithium batteries of Example 1 and the cellulose-based separator;
[0039] Figure 5 This is a comparison chart of the cycle performance of the flame-retardant cellulose-based diaphragm for lithium batteries in Example 1 and the cellulose-based diaphragm. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0041] like Figure 1 FIG. 1 is an operation flow chart of a method for preparing a flame-retardant cellulose-based diaphragm for a lithium battery provided by the present invention, and the process includes the following specific steps:
[0042] S10: adding anhydrous ethanol into the flask containing 4-aminopyridine, heating and stirring until it is completely dissolved;
[0043] S20: adding anhydrous potassium carbonate to the mixed solution to form a mixed solution;
[0044] S30: adding the chlorobenzene solution containing hexachlorocyclotriphosphazene to the mixed solution, and stirring for a certain period of time to react;
[0045] S40: repeatedly filtering and extracting the crude product obtained by the reaction through chlorobenzene and ethanol;
[0046] S50: soaking the cellulose diaphragm dried in advance with the filtrate to obtain a flame retardant cellulose-based diaphragm.
[0047] Among them, in the above technical scheme, anhydrous ethanol is added to a flask containing 4-aminopyridine, and in the step of heating and stirring until complete dissolution, the mass ratio of anhydrous ethanol to 4-aminopyridine is 20-25:1-4, more preferably 23-24:2-3, and more preferably 23.679:2.918.
[0048] Furthermore, in the above technical solution, anhydrous ethanol is added to a flask containing 4-aminopyridine, and heated and stirred until completely dissolved, and the heating temperature is 30-60°C, more preferably 30-50°C, and more preferably 40°C.
[0049] Furthermore, in the above technical solution, anhydrous potassium carbonate is added to the above mixed solution, and the mass ratio of anhydrous potassium carbonate to 4-aminopyridine is 3-6:1-4, more preferably 4-5:2-3, and more preferably 4.837:2.918.
[0050] Furthermore, in the above technical scheme, a chlorobenzene solution containing hexachlorocyclotriphosphazene is added to the mixed solution, and in the reaction step of stirring for a certain time, the mass ratio of chlorobenzene, hexachlorocyclotriphosphazene and 4-aminopyridine is 10-15:1-4:1-4, more preferably 10-12:1-3:2-3; more preferably 11.075:1.738:2.918.
[0051] Furthermore, in the above technical solution, the chlorobenzene solution containing hexachlorocyclotriphosphazene is added to the mixed solution and stirred for a certain period of time to react, and the stirring time is 1 to 3 hours, more preferably 1 to 2 hours, and more preferably 1 hour.
[0052] Furthermore, in the above technical scheme, the crude product obtained by the reaction is repeatedly filtered and extracted with chlorobenzene and ethanol, and the volume ratio of anhydrous ethanol to chlorobenzene during the filtration process is 40-60:10-20; the number of filtrations is 1 to 10 times, more preferably 1 to 5 times, and more preferably 3 times.
[0053] Furthermore, in the above technical solution, during the soaking process of the pre-dried cellulose membrane in the filtrate, the cellulose membrane is soaked in the filtrate for 1 to 5 hours, more preferably 1 to 3 hours, and more preferably 2 hours; the cellulose membrane is soaked 1 to 5 times, more preferably 2 to 4 times, and more preferably 3 times.
[0054] The present invention provides an application of a flame retardant cellulose-based diaphragm for a lithium battery. In this embodiment, the flame retardant cellulose-based diaphragm is used to assemble a lithium ion battery, and after standing for a period of time, a flame retardant cellulose-based LIB diaphragm is obtained.
[0055] Furthermore, in the above technical solution, the density of the flame retardant cellulose-based LIB separator is 0.3-0.6 g / cm3 , preferably 0.4 to 0.6 g / cm 3 , more preferably 0.5 g / cm 3 .
[0056] The cellulose-based separator includes a cellulose-based separator made of natural fiber or artificial fiber.
[0057] Example 1
[0058] This embodiment provides a flame retardant cellulose-based separator for a lithium battery, and a preparation method thereof comprises the following steps:
[0059] (1) 4-APD (2.918 g) was added to a three-necked round-bottom flask equipped with a mechanical stirrer and containing 23.679 g of anhydrous ethanol solution, and completely dissolved at 40°C;
[0060] (2) adding anhydrous potassium carbonate (4.837 g) to the above mixed solution;
[0061] (3) Add a chlorobenzene solution (10 ml) containing hexachlorocyclotriphosphazene (1.738 g) to the above solution and stir for 1 h;
[0062] (4) The crude product obtained by the reaction was repeatedly filtered and extracted with chlorobenzene (10 ml) and ethanol (50 ml). The filtrate was used to soak the cellulose membrane dried in advance for 3 times, each soaking time was 2 hours, and a flame-retardant cellulose-based membrane was obtained.
[0063] Table 1: Porosity and electrolyte absorption of polyolefin separators and flame-retardant cellulose-based separators
[0064]
[0065] It can be seen from the table that compared with traditional polyolefin separators, the prepared flame-retardant cellulose-based separators have higher porosity and electrolyte absorption rate and smaller density, and have great application potential in the field of lithium-ion batteries.
[0066] The contact angle diagram of the flame-retardant cellulose-based separator for lithium batteries prepared above is shown in Figure 2 As shown, it can be found that the contact angle of the flame-retardant cellulose-based separator for lithium batteries is only 15.1°, which is much smaller than the electrolyte contact angle of the commercial separator (Celgard 2320), indicating that it has higher wettability with the electrolyte and has the potential to be used as a lithium battery separator.
[0067] The thermal stability of the flame-retardant cellulose-based separator of the lithium battery prepared above was tested, and the results were as follows: Figure 3 As shown. Figure 3It can be seen that Celgard 2320 showed the lowest residual mass (7.4%) after the experiment, indicating its poor thermal stability. The residual mass of the flame retardant cellulose-based separator after the test was as high as 43.2%, indicating its excellent thermal stability.
[0068] The flame-retardant cellulose-based diaphragm prepared above was used to assemble lithium-ion batteries, and the comparison chart of the first charge and discharge capacity was as follows: Figure 4 As shown. The initial discharge capacity of the half-cell using Celgard 2320 is 384.7 mAh / g, which is slightly higher than that of the flame-retardant cellulose-based LIB (379.2 mAh / g). This result shows that the flame-retardant cellulose-based separator has electrochemical performance that is no less than that of the traditional commercial separator. In addition, the half-cell with flame-retardant cellulose-based LIB exhibits a smaller voltage platform than Celgard 2320 in the initial charge and discharge cycle, which is due to its excellent separator wettability.
[0069] The flame-retardant cellulose-based diaphragm prepared above was used to assemble lithium-ion batteries, and the cycle performance comparison results were shown in the following figure: Figure 5 As shown. The flame-retardant cellulose-based LIB exhibited a high initial discharge capacity of 315.6 mAh / g and an average coulombic efficiency of 99.3% during the 0.3C cycle, while the initial discharge capacity and average coulombic efficiency of the commercial separator were 296.1 mAh / g and 99.1%, respectively. In addition, after 100 cycles, the flame-retardant cellulose-based LIB also showed good cycle stability and a high capacity retention rate of 99.1%, indicating the excellent electrochemical performance of the flame-retardant cellulose-based separator.
[0070] Example 2
[0071] This embodiment provides a flame retardant cellulose-based separator for a lithium battery, and a preparation method thereof comprises the following steps:
[0072] (1) Add 4-APD (2 g) into a three-necked round-bottom flask equipped with a mechanical stirrer and containing 20 g of anhydrous ethanol solution and completely dissolve it at 50°C;
[0073] (2) adding anhydrous potassium carbonate (4 g) to the above mixed solution;
[0074] (3) Add a chlorobenzene solution (10 ml) containing hexachlorocyclotriphosphazene (1 g) to the above solution and stir for 2 h;
[0075] (4) The crude product obtained by the reaction was repeatedly filtered and extracted with chlorobenzene (10 ml) and ethanol (40 ml). The filtrate was used to soak the cellulose membrane dried in advance twice, each soaking time was 1 hour, to obtain a flame-retardant cellulose-based membrane.
[0076] Example 3
[0077] This embodiment provides a flame retardant cellulose-based separator for a lithium battery, and a preparation method thereof comprises the following steps:
[0078] (1) Add 4-APD (2.5 g) into a three-necked round-bottom flask equipped with a mechanical stirrer and containing 25 g of anhydrous ethanol solution and completely dissolve it at 35°C;
[0079] (2) adding anhydrous potassium carbonate (4.5 g) to the above mixed solution;
[0080] (3) Add a chlorobenzene solution (10 ml) containing hexachlorocyclotriphosphazene (1.5 g) to the above solution and stir for 0.5 h;
[0081] (4) The crude product obtained by the reaction was repeatedly filtered and extracted with chlorobenzene (10 ml) and ethanol (45 ml). The filtrate was used to soak the cellulose membrane dried in advance twice, each soaking time was 1.5 hours, and a flame-retardant cellulose-based membrane was obtained.
[0082] Example 4
[0083] This embodiment provides a flame retardant cellulose-based separator for a lithium battery, and a preparation method thereof comprises the following steps:
[0084] (1) 4-APD (3 g) was added to a three-necked round-bottom flask equipped with a mechanical stirrer and containing 30 g of anhydrous ethanol solution, and completely dissolved at 50°C;
[0085] (2) adding anhydrous potassium carbonate (5 g) to the above mixed solution;
[0086] (3) Add a chlorobenzene solution (10 ml) containing hexachlorocyclotriphosphazene (2 g) to the above solution and stir for 1 h;
[0087] (4) The crude product obtained by the reaction was repeatedly filtered and extracted with chlorobenzene (10 ml) and ethanol (60 ml). The filtrate was used to soak the cellulose membrane dried in advance for 5 times, each soaking time was 3 hours, to obtain a flame-retardant cellulose-based membrane.
[0088] Specifically, the principle of the present invention is: adding anhydrous ethanol to a flask containing 4-aminopyridine, heating and stirring until it is completely dissolved; adding anhydrous potassium carbonate to the above mixed solution to form a mixed solution; adding a chlorobenzene solution containing hexachlorocyclotriphosphazene to the solution, stirring for a certain period of time; repeatedly filtering and extracting the crude product obtained by the reaction through chlorobenzene and ethanol; taking the filtrate to soak a cellulose diaphragm that has been dried in advance to obtain a flame-retardant cellulose-based diaphragm.
Claims
1. A method for preparing a flame-retardant cellulose-based diaphragm for a lithium battery, characterized in that: The specific steps include: S10: adding anhydrous ethanol into the flask containing 4-aminopyridine, heating and stirring until it is completely dissolved; S20: adding anhydrous potassium carbonate to the mixed solution to form a mixed solution; S30: adding a chlorobenzene solution containing hexachlorocyclotriphosphazene to the mixed solution, and stirring for a certain period of time to react; S40: repeatedly filtering and extracting the crude product obtained by the reaction through chlorobenzene and ethanol; S50: soaking the cellulose diaphragm dried in advance with the filtrate to obtain a flame-retardant cellulose-based diaphragm; In the step of adding anhydrous ethanol to a flask containing 4-aminopyridine and heating and stirring until completely dissolved, the mass ratio of anhydrous ethanol to 4-aminopyridine is 20-25:1-4; The step of adding anhydrous ethanol to a flask containing 4-aminopyridine and heating and stirring until the flask is completely dissolved, wherein the heating temperature is 30-60°C; The anhydrous potassium carbonate is added to the mixed solution, and the mass ratio of the anhydrous potassium carbonate to the 4-aminopyridine is 3-6:1-4; In the step of adding the chlorobenzene solution containing hexachlorocyclotriphosphazene to the mixed solution and stirring for a certain period of time, the mass ratio of chlorobenzene, hexachlorocyclotriphosphazene and 4-aminopyridine is 10-15:1-4:1-4.
2. The method for preparing a flame-retardant cellulose-based separator for a lithium battery according to claim 1, characterized in that: In the process of adding the chlorobenzene solution containing hexachlorocyclotriphosphazene into the mixed solution and stirring for a certain time to react, the stirring time is 1 to 3 hours.
3. The method for preparing a flame-retardant cellulose-based separator for a lithium battery according to claim 2, characterized in that: The crude product obtained by the reaction is repeatedly filtered and extracted with chlorobenzene and ethanol, and the volume ratio of anhydrous ethanol to chlorobenzene is 40-60:10-20 during the filtration process; the number of filtrations is 1-5 times.
4. The method for preparing a flame-retardant cellulose-based separator for a lithium battery according to claim 3, characterized in that: In the soaking process of soaking the cellulose membrane dried in advance with the filtrate, the cellulose membrane is soaked in the filtrate for 1 to 5 hours and the number of times the cellulose membrane is soaked is 1 to 5 times.
5. An application of a flame retardant cellulose-based diaphragm for a lithium battery prepared by the method for preparing a flame retardant cellulose-based diaphragm for a lithium battery according to any one of claims 1 to 4, wherein the flame retardant cellulose-based diaphragm is used to assemble a lithium-ion battery, and a flame retardant cellulose-based LIB diaphragm is obtained after standing for a period of time.
6. The use of a flame-retardant cellulose-based separator for lithium batteries according to claim 5, characterized in that: The density of the flame-retardant cellulose-based LIB separator is 0.3-0.6 g / cm 3 .
Citation Information
Patent Citations
Preparation method of cellulose diaphragm for lithium battery
CN115498358A
Multi-dimensional carbon price prediction method based on CEEMDAN and AE-TCN
CN116823313A
Flame-retardant cellulose membrane for lithium battery and preparation method of membrane
CN103579562A
Metal complex flame retardant and preparation method thereof
CN107344998A